THE EFFECT OF DIVERSE FERTILIZERS ON THE QUALITY OF BEGONIA SEMPERFLORENS LINK. ET OTTO. - Margarita Davitkovska; Zvezda Bogevska; Gordana Popsimonova; Rukie Agic; Ana Vujošević; Svjetlana Zeljković; Boris Dorbić (My University, 2022)
This research was carried out to analyze the effect of diverse types of fertilizers and concentrations on the morphological features of Begonia semperflorens Link. et Otto., as well as to determine the most appropriate concentration of fertilizer to obtain the highest plant quality. Different types of liquid fertilizers and concentrations were used in this experiment - Agrosal with NPK 10-5-5 + microelements (0.2%; 0.3%; 0.4%), Agrosal with NPK 7-1-5 + microelements (0.2%; 0.3%; 0.4%) and Agrosal with NPK 12-5-7 + microelements (0.2%; 0.3%; 0.4%). For measurement, 30 plants were used per treatment, three months after planting into plastic containers. The following biometric parameters were analyzed: plant height (mm), number of leaves, number of branches, and number of inflorescences. Measurements of biometric parameters showed that the liquid mineral fertilizer Agrosal with NPK 12-5-7 + microelements and a concentration of 0.4% showed the highest average number of branches and number of inflorescences. Agrosal with NPK 12-5-7 + microelements and concentration of 0.3% showed the highest average height of plant and Agrosal with NPK 7-1-5 + microelements and concentration of 0.2% showed the highest average number of leaves. Agrosal with NPK 12-5-7 + microelements and a concentration of 0.4% can be recommended in practice.
Keywords: biometric parameters, concentration, morphological features, plants